2013
DOI: 10.5114/wo.2013.38805
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of real-world usage of lanreotide AUTOGEL 120 in Polish acromegalic patients – results from the prospective 12-months phase of Lanro-Study

Abstract: Aim of the studyTo assess resource utilization and costs of treatment with lanreotide AUTOGEL 120 mg (ATG120) administered as part of routine acromegaly care in Poland.Material and methodsA multicentre, non-interventional, observational study on resource utilization in Polish acromegalic patients treated with ATG120 at 4 weeks or extended (> 4 weeks) dosing interval. The study recruited adult acromegalic patients treated medically for ≥ 1 year including at least 3 injections of ATG120. Data on dosing interval,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 10 publications
5
8
0
Order By: Relevance
“…ATG120 was predominantly administered in an outpatient setting by a health care professional. The results obtained during two years were consistent with those described in interim analysis with follow-up of one year [6]. This analysis revealed that 50% of patients received ATG120 at an extended dosing interval, and the mean number of days between injections was 35.6 (SD 8.4).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…ATG120 was predominantly administered in an outpatient setting by a health care professional. The results obtained during two years were consistent with those described in interim analysis with follow-up of one year [6]. This analysis revealed that 50% of patients received ATG120 at an extended dosing interval, and the mean number of days between injections was 35.6 (SD 8.4).…”
Section: Discussionsupporting
confidence: 77%
“…This analysis revealed that 50% of patients received ATG120 at an extended dosing interval, and the mean number of days between injections was 35.6 (SD 8.4). ATG120 was predominantly administered in an outpatient setting (77%) by a health care professional (94%) [6]. When interpreting the results of this study it is important to note the three following assets: First, the results have been obtained from a prospective study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a growing body of evidence, including an expert consensus statement [4], suggests that extended dosing intervals (EDIs) with lanreotide autogel 120 mg of up to 8 weeks (versus the standard 4-week dosing interval) may be equally effective in patients who have achieved good biochemical control with long-acting SSAs [8][9][10]. The most relevant benefits of extending the treatment interval are fewer injections, lower costs, more convenient treatment; in addition, EDIs and/or dose reductions have both been shown to reduce the risk of treatment-related side-effects [3,4,9,11]. Numerous open-label trials have shown that lanreotide autogel 120 mg administered at dosing intervals >4 weeks provides comparable biochemical control to that achieved with standard dosing intervals [4,[9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%